2014
DOI: 10.1523/jneurosci.2329-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

SLC30A10 Is a Cell Surface-Localized Manganese Efflux Transporter, and Parkinsonism-Causing Mutations Block Its Intracellular Trafficking and Efflux Activity

Abstract: Manganese (Mn) is an essential metal, but elevated cellular levels are toxic and may lead to the development of an irreversible parkinsonian-like syndrome that has no treatment. Mn-induced parkinsonism generally occurs as a result of exposure to elevated Mn levels in occupational or environmental settings. Additionally, patients with compromised liver function attributable to diseases, such as cirrhosis, fail to excrete Mn and may develop Mn-induced parkinsonism in the absence of exposure to elevated Mn. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
300
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(316 citation statements)
references
References 53 publications
16
300
0
Order By: Relevance
“…We closely examined its localization using a surface biotinylation assay with a membrane-impermeable biotinylation reagent and found the biotinylated hZnT10 protein in the cell surface fractions, which confirms that hZnT10 is localized on the cell surface, as reported previously (Fig. 2G) (25). However, the current data cannot be used to infer the relative distribution of hZnT10 between the Golgi apparatus and the plasma membrane because hZnT10 was overexpressed under the control of the strong ␤-actin promoter (30), which limits our ability to deter-mine whether manganese efflux occurred from the plasma membrane or via a secretory pathway through the Golgi.…”
Section: Evaluation Of Manganese Detoxification/efflux Protein Functisupporting
confidence: 88%
See 1 more Smart Citation
“…We closely examined its localization using a surface biotinylation assay with a membrane-impermeable biotinylation reagent and found the biotinylated hZnT10 protein in the cell surface fractions, which confirms that hZnT10 is localized on the cell surface, as reported previously (Fig. 2G) (25). However, the current data cannot be used to infer the relative distribution of hZnT10 between the Golgi apparatus and the plasma membrane because hZnT10 was overexpressed under the control of the strong ␤-actin promoter (30), which limits our ability to deter-mine whether manganese efflux occurred from the plasma membrane or via a secretory pathway through the Golgi.…”
Section: Evaluation Of Manganese Detoxification/efflux Protein Functisupporting
confidence: 88%
“…Recent significant findings show that loss-of-function mutations of the ZnT10/SLC30A10 gene result in parkinsonism with hypermanganesemia, a syndrome of hepatic cirrhosis, polycythemia, and dystonia (22,23). ZnT10 is localized to the plasma membrane and is functional in manganese metabolism by effluxing cytosolic manganese (24,25). ZnT10 is also involved in zinc homeostasis in subcellular localization (26,27).…”
mentioning
confidence: 99%
“…IIIA). The ability of ZnT10 to transport manganese has been shown recently at the molecular level (237). ZnT10 mRNA expression is high in the liver and brain, which is consistent with high manganese accumulation in these tissues for patients with ZnT10 mutations (341, 417).…”
Section: Znt10mentioning
confidence: 62%
“…Using a combination of mechanistic and functional studies in cell culture (HeLa and AF5 cells), Caenorhabditis elegans (C. elegans) and mouse primary midbrain neurons, we showed that SLC30A10 functions primarily as an exporter at the cell membrane to transport cytoplasmic Mn ions across the membrane to the extracellular space, thus reducing intracellular Mn levels and protecting against Mn-induced toxicity. 23 Further, we discovered that the disease-causing SLC30A10 mutants (L89P, D98-134, D105-107, T196P and Q308Stop) failed to traffic to the cell surface, and instead, were trapped in the ER. 23 Importantly, our results revealed that these mutant proteins also failed to mediate Mn efflux.…”
Section: Identification Of Slc30a10mentioning
confidence: 99%
“…23 Further, we discovered that the disease-causing SLC30A10 mutants (L89P, D98-134, D105-107, T196P and Q308Stop) failed to traffic to the cell surface, and instead, were trapped in the ER. 23 Importantly, our results revealed that these mutant proteins also failed to mediate Mn efflux. 23 In C. elegans exposed to 100 and 200 mM of MnCl 2 , expression of WT-SLC30A10 significantly increased worm survival rate when compared with control worms, while the disease-causing mutant L89P had no effect.…”
Section: Identification Of Slc30a10mentioning
confidence: 99%